1986
DOI: 10.1021/ma00166a001
|View full text |Cite
|
Sign up to set email alerts
|

Polymerization of ethylene and propylene with chromium tristearate/diethylaluminum chloride/metal chloride catalysts

Abstract: A CrtCnH^COOls/AlEtsCl/MgC^catalyst was prepared by modifying the Battelle-type catalyst with MgCl2 dissolved in 2-ethyl-l-hexanol (2-EHA), and the polymerization of ethylene was carried out in toluene at 20-40 °C. The rate of polymerization markedly increased with increasing Mg/Cr molar ratio. The polyethylene obtained without MgCl2 had a very broad polydispersity, whereas the polyethylenes in the presence of MgCl2 had extremely high molecular weights with narrow polydispersities. The polymerization of ethyle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…The Cr-(acac) 3 /MgCl 2 -DEAC catalyst system produced the highest molecular weight polypropylene with a fairly high activity, however, the resulting polymer contained a considerable amount of atactic polymer. Taking into account that the addition of suitable Lewis bases as internal and/ or external donors improves the isospecificity of ordinary Ziegler-Natta catalysts, [14] ethyl benzoate (EB), di-i-propyldimethoxysilane (DIPDMS), and dibutylphtalate (DNBP) were introduced as an external donor to the Cr-(acac) 3 /MgCl 2 -DEAC catalyst system. As expected, a drastic increase in catalyst activity and isospecificity was observed by adding ethylbenzoate (EB) as an external donor (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Cr-(acac) 3 /MgCl 2 -DEAC catalyst system produced the highest molecular weight polypropylene with a fairly high activity, however, the resulting polymer contained a considerable amount of atactic polymer. Taking into account that the addition of suitable Lewis bases as internal and/ or external donors improves the isospecificity of ordinary Ziegler-Natta catalysts, [14] ethyl benzoate (EB), di-i-propyldimethoxysilane (DIPDMS), and dibutylphtalate (DNBP) were introduced as an external donor to the Cr-(acac) 3 /MgCl 2 -DEAC catalyst system. As expected, a drastic increase in catalyst activity and isospecificity was observed by adding ethylbenzoate (EB) as an external donor (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…45 wt.-% of isotacticity. [10] Similar catalysts using b-diketonates as ligands were prepared by Asanuma et al and were used for ethylene homopolymerization and ethylene-propylene copolymerization. [11] More recently, we have investigated the propylene polymerization with the chromium(III) acetylacetonate (Cr(acac) 3 )/MgCl 2 -DEAC catalyst system and found that the addition of suitable Lewis bases like ethylbenzoate (EB) largely increases the polymerization activity as well as the isospecificity of the catalytic system.…”
Section: Introductionmentioning
confidence: 99%
“…Although the primary commercial use of the Phillips catalyst is for the polymerization of ethylene and ethylene with α-olefins, the catalyst will also homopolymerize other unsaturates, including acetylenes [157,158,207] and α-olefins, such as propylene, butene and hexene [2,7,30,[324][325][326][327][328][329][330][331][332]. Like Ziegler-Natta catalysts, certain adjuvants can be used with Cr/silica to improve the stereoselectivity [333].…”
Section: Short Chain Branchingmentioning
confidence: 99%